THE EFFECT OF GROWTH OPPORTUNITY, LEVERAGE, AND DIVIDEND ON INVESTMENT DECISIONS IN INDUSTRIAL SECTOR COMPANIES BEI REGISTERED PHARMACY PERIOD 2015-2019 - Muhanniah; Muhammad Ali; Erlina Pakki (Journal of Accounting Issues, 2023)
The organization's management is required to make a number of financial decisions, including investment decisions. For making investment decisions, factors from within the company, like growth potential, leverage, and dividends, are taken into account in this study. This study proposes to examine the effects of growth potential, leverage, and dividends on investment decisions. Companies that have become public and are listed in Indonesia for the years of 2015 to 2019 a company called the primary focus of this researcher's research in the pharmaceutical industry area was exchange. The methodology employed is secondary data research with a quantitative approach. Purposive sampling was used, and a sample size of 35 enterprises was used. Multiple-linear-regression is the approach taken to analyze the data. According to the study's conclusions, it is obvious that.